PROGRAM PENDIDIKAN AKHLAK UNTUK PENDIDIK SETINGKAT SMP DAN SMA DI PONDOK PESANTREN - Ruri Syamsul Rizal; Akhmad Alim; Ahmad Ahmad (Tarbiyatuna Kajian Pendidikan Islam, 2023)
Ideally, an educator in a pesantren should be a good role model for his students. However, in reality, today there are many cases of morals in Islamic boarding schools which are carried out by an educator. Beating students, extortion, to immoral acts against students and female students. The purpose of this research is to research and develop a moral education program for educators by returning an educator's certificate. This research uses a qualitative approach with a type of field research. The process of collecting data is used by observing, interviewing, and documenting. Data analysis techniques obtained by the process of searching and systematically compiling data? obtained from the results of interviews, field notes and documentation. The results of the study show, first, the moral education program for educators at the As-Syifa Subang Islamic boarding school has the goal of strengthening the spiritual competence of educators, sharpening the vision, mission and goals of the Islamic boarding school, reviving the heart, and others. Strategies used with ta`lim, habituation, exemplary, reward and punishment, discipline, and enforcement of rules, evaluation system by including all these activities in the performance of educators and competency tests. Second, the moral education program for educators at Daarut Tauhiid Bandung has the goal of strengthening the spiritual competence of an educator through the habit of worship, equating HR quality standards, having BAKU (good and strong) character/morals, Daarut Tauhid culture. The strategies used are ta`lim, habituation, exemplary, reward and punishment, discipline, and enforcement of rules. Evaluation system by including all these activities in educator performance and competency tests. Third, the Moral Education Program for educators in Islamic boarding schools has a goal, namely: strengthening the spiritual competence of an educator who has a straight and strong faith, true worship, broad-mindedness, and noble character. The strategies used are ta`lim, habituation, exemplary, reward and punishment, discipline, prayer and enforcement of rules. Involvement in performance entry activities and competency tests.